Giuseppa Di Sano: A Woman at the Origins of Civil Antimafia (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The paper introduces the document concerning the testimony of Giuseppa Di Sano, attached to the one of prefect Ermanno Sangiorgi in Palermo on 20 November 1898. Pushed not only from mother love, but also for protecting her business activity and her dignity. she found the courage to suit the mafia for the killing of her daughter Emanuela.
Keywords: mafia; women; rebellion; justice; violence